Supplemental thiamine for the treatment of acute heart failure syndrome: a randomized controlled trial - Howard A. Smithline; Michael Donnino; Fidela S. J. Blank; Richard Barus; Ryan A. Coute; Alexander B. Knee; Paul Visintainer (BMC, 2019)
Abstract Background The purpose of this pilot study was to determine if a definitive clinical trial of thiamine supplementation was warranted in patients with acute heart failure. We hypothesized that thiamine, when added to standard of care, would improve dyspnea (primary outcome) in hospitalized patients with acute heart failure. Peak expiratory flow rate, type B natriuretic peptide, free fatty acids, glucose, hospital length of stay, as well as 30-day rehospitalization and mortality were pre-planned secondary outcome measures. Methods This was a blinded experimental study at two urban academic hospitals. Consecutive patients admitted from the Emergency Department with a primary diagnosis of acute heart failure were recruited over 2 years. Patients on a daily dietary supplement were excluded. Randomization was stratified by type B natriuretic peptide and diabetes medication categories. Subjects received study drug (100 mg thiamine or placebo) in the evening of their first and second day. Outcome measures were obtained 8 h after study drug infusion. Dyspnea was measured on a 100-mm visual analog scale sitting up on oxygen, sitting up off oxygen, and lying supine off oxygen with 0 indicating no dyspnea. Data were analyzed using mixed-models as well as linear, negative binomial and logistic regression models to assess the impact of group on outcome measures. Results Of 130 subjects randomized, 118 had evaluable data (55 in the control and 63 in the treatment groups), 89% in both groups were adjudicated to have primarily AHF. Thiamine values increased significantly in the treatment group and were unchanged in the control group. One patient had thiamine deficiency. Only dyspnea measured sitting upright on oxygen differed significantly by group over time. No change was found for the other measures of dyspnea and all of the secondary measures. Conclusions In mild-moderate acute heart failure patients without thiamine deficiency, a standard dosing regimen of thiamine did not improve dyspnea, biomarkers, or other clinical parameters. Trial registration ClinicalTrials.gov: NCT00680706, May 20, 2008 (retrospectively registered).